"It brings the community together": Benefits from local park and recreation renovations. Issue 5 (20th October 2018) - Mullenbach, Lauren E.; Pitas, Nicholas A. D.; Walker, Joseph; Mowen, Andrew J.
ABSTRACT: As public dollars for parks and recreation become increasingly scarce, empirical evidence of community benefits from capital investments becomes more important. However, measuring impacts of parks and recreation investments can be costly and difficult for local park agencies. This study presents an alternative approach to assessing community response to parks and recreation center renovations. Results of three renovation case studies indicate favorable impacts from investment. Data were collected with a new survey instrument, developed to allow local stakeholders to perform retrospective evaluations of renovations and share their perspectives. Residents perceived the study sites were better maintained (52% strongly agree) and more appealing to broad cross-sections of the community (39% strongly agree). Open-ended responses revealed five themes: study sites became destinations for families, provided sense of community, facilitated positive health outcomes, became neighborhood assets, and provided community benefits. Implications for community agencies and organizations and recommendations for the tool's improvement are discussed.